Behavioural Investor Individual in Capital Stock Indonesia: DISC Personality, Market and Accounting Information (International Journal of Applied Research in Management and Economics, 2020)
Every individual investor has an error in making a decision to buy or sell shares. Mistakes in making predictions can be minimized by understanding his personality and the steps taken in getting better returns. This study uses Analytical Hierarchy Process (AHP), secondary data, Focus Group Discussion (FGD), and stock simulations emphasizing the decision-making process when buying and selling shares. The initial AHP model gives the results of the target shares purchased, accounting information selected Price Book Value (PBV) that is undervalued, Return on Assets (ROA) around 10-20 percent, Return in Equity (ROE) around 20-40 percent, type of ownership Indonesian SOEs selected stocks for the long term, while short-term tend to be private, and use technical analysis by looking at the upward trend that is using moving average indicators, MA5 above MA20. As a result, individual stock investors who have only become stock investors for less than 1 year have stock returns of around 2-4 percent, already become investors, 1-3 years will get a return of around 10 percent, stock returns will rise again, long-term investments will be made. around 20 percent. The risk for short-term investment will be greater than the long-term investment. The DISC personality that fits this stage is precisionist.